Geospatial Analysis of Flight Destinations: a Study of Flight Patterns from Tucson, AZ, Jackson, MS, and Appleton, WI. - Olson, Lindsay M. (My University, 2009)
Studies on air traffic flows in the United States have generally focused on hubs. When origin/destination traffic is analyzed at the final destination level a more nuanced picture emerges. This study looks at the final destination cities for flights orginating in Tucson, AZ; Jackson, MS; and Appleton, WI.
Color poster with text, maps, and graphs.
Keywords: Air travel--United States--Models; Origin and destination traffic surveys--United States; Posters